Methods of Physical Recreation of Students Trained in Kickboxing Section - C. А. Пашкевич; Е. В. Крюков (Physical Education Theory and Methodology, 2016)
Research objective: to evaluate the effectiveness of implementing sports massage in recreation of kickboxing students to improve their sports performance.